A Minus-End–directed Kinesin with Plus-End Tracking Protein Activity Is Involved in Spindle Morphogenesis - Ambrose, J. Christian (The American Society for Cell Biology, 2005)
Diverse kinesin motor proteins are involved in spindle function; however, the mechanisms by which they are targeted to specific sites within spindles are not well understood. Here, we show that a fusion between yellow fluorescent protein (YFP) and a minus-end–directed Kinesin-14 (C-terminal family) from Arabidopsis, ATK5, localizes to mitotic spindle midzones and regions rich in growing plus-ends within phragmoplasts. Notably, in Arabidopsis interphase cells, YFP::ATK5 localizes to microtubules with a preferential enrichment at growing plus-ends; indicating ATK5 is a plus-end tracking protein (+TIP). This +TIP activity is conferred by regions outside of the C-terminal motor domain, which reveals the presence of independent plus-end tracking and minus-end motor activities within ATK5. Furthermore, mitotic spindles of atk5 null mutant plants are abnormally broadened. Based on these data, we propose a model in which ATK5 uses plus-end tracking to reach spindle midzones, where it then organizes microtubules via minus-end–directed motor activity.